Office space, a company's frontier : the corporate decision to buy or lease - Furfine, Craig (London : Kellogg School of Management, 2016)
Markus Steuer, director of real estate at Drechtal Pharmaceuticals, must decide where his firm should locate in the immediate future. Drechtal was currently leasing space in seven different buildings, yet the company anticipated a dramatic increase in headcount should its first oncology drug, Trianoline, be approved by Swissmedic. The potential increased demand for space initiated Steuer's investigation of whether it was optimal to continue to lease space or whether or not it should invest in its own corporate headquarters. With its current leases set to expire over the coming 24 months, it was an opportune time to consider Drechtal's options.
Originally published in Furfine, C. (2016). Office space, a company's frontier: The corporate decision to buy or lease. 5-315-500. Evanston, IL: Kellogg School of Management at Northwestern University.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Lease or buy decisions -- Case studies; Real property -- Case studies